Óleo essencial de aloysia triphylla em juvenis de jundiá (Rhamdia quelen) intoxicados com ocratoxina A - Camargo, Flávia Constância de Los Santos de (2021)
The objective of this study was to analyze the impact of the use of Aloysia triphylla essential oil (OEAT) at a concentration of 2 mL/Kg, added to the feed of dentex (Rhamdia quelen) against ochratoxin A intoxication in two concentrations (200 and 400 µg/Kg). Male and female fry (R. quelen) fed diets containing ochratoxin A were used to evaluate liver and kidney damage and growth parameters. The fish were divided into six treatments with three repetitions; each treatment was individualized in a closed recirculation system consisting of 3 boxes, and a total of 18 boxes containing 40L of water containing seven fish per repetition were used. The treatments were as follows: Control; OEAT 2 mL/Kg, 200µg ochratoxin + OEAT 2 mL/Kg; 400µg ochratoxin + OEAT 2 mL/Kg and 200µg ochratoxin and 400µg ochratoxin without the presence of OEAT. The experiment lasted 32 days and on the last day of the experiment the animals were weighed, slaughtered and whole blood was collected for processing and plasma was obtained for plasma analysis of enzymes and metabolites indicators of kidney and liver damage. The levels of TGO and TGP were evaluated as indicators of hepatic damage and the treatment with 400 µg/Kg of ochratoxin A without the essential oil obtained a significant superior difference in relation to the two enzymes, indicating that the use of the essential oil of A. triphylla in the concentration of 2 mL/Kg protected the group treated with 400 µg/Kg of ochratoxin A associated with OEAT from hepatic damage. The creatinine level obtained significant higher difference only in the group treated with 400µg of OTA+OEAT, demonstrating a possibly synergistic effect. The total protein value differed statistically lower only in the 2 mL/Kg OEAT group. The parameters of growth, lactate and mortality were not significantly different. Therefore, we conclude that the use of OEAT at a concentration of 2 mL/Kg in juvenile dolphins is beneficial in relation to liver protection caused by ochratoxin A.